Cobalt and Iron Complexes with N-heterocyclic Ligands as Pyrolysis Precursors for Oxygen Reduction Catalysts - Roncaroli, Federico (2015)
Cobalt and Iron based catalysts for the Oxygen Reduction Reaction (ORR) are a promising alternative to the use of Pt in Polymer Electrolyte Fuel Cells (PEMFC). A systematic study on the influence of the nitrogenated ligand in the precursor complex on the ORR activity was performed. Several Fe and Co complexes were prepared with different N-heterocyclic ligands, namely: meso-tetra-(4-carboxyphenyl)-porphyrin (TCPP), N-methylimidazole (N-Me-Im), 3-amino-1,2,4-triazole-5-carboxylic acid (ATZC), 2,2′-bis(4,5-dimethylimidazole) (bis-Me-Im), phenanthroline (phen), 2-pyrazinecarboxylic acid (CO2-Pz), 3,6-di-2-pyridyl-1,2,4,5-tetrazine (DPTZ) and 2,4,6-tri(2-pyridyl)-s-triazine (TPTZ), adsorbed on a carbon substrate and submitted to thermal treatment. These ligands comprise five and six membered rings with one to four N-atoms. Key parameters such as the pyrolysis temperature, the complex load and the metal: ligand ratio were studied, in order to optimize the efficiency of the catalysts. The synthesized catalysts were characterized by several physical bulk and surface techniques, namely XRD, TGA, Raman spectroscopy, XPS, EDX and electron microscopies (SEM and TEM). The best catalyst was obtained from a Cobalt-phenanthroline precursor, adsorbed on a mesoporous carbon material, and pyrolyzed at 700 °C. The equilibrium potential was 0.90 V vs NHE (1.0 V for Pt), exchange current density 25 μA cm−2, Tafel slope was 90 mV dec−1, and 4.0 exchanged electrons, less than 9 % in H2O2 yield, and half wave potential only 80 mV lower than that of Platinum (10%). This catalyst exhibited the highest N content as determined by XPS. The electrochemical data of the prepared catalysts were analyzed in the context of the TGA, XRD and XPS information. A correlation between ORR activity and the N content (XPS) was found. This result strongly supports the model that proposes N atoms as the active sites, and provides a rational tool for designing new catalysts.